A atividade portuária de transporte e armazenagem de granel no Porto de Santos, a poluição atmosférica por material particularizado e a responsabilização pelo dano. - Bomfim, Juliana Campos (2014)
This study discusses the interference of the port activities, specifically the transportation and solid bulk cargo storage vegetable origin, which has caused serious threats to the environment and quality of life of the local population to Porto. The city of Santos, home to the largest national port, which is also considered the largest port in extension and ability to export and storage of cargo in Latin America, has been feeling the environmental impacts of the activities a few years ago; the movement of dry bulk made in terminals installed in Ponta da Praia _ neighborhood region is largely responsible for the emission and dispersion of particulate matter in the atmosphere, causing bad smell and cardiorespiratory problems in the population. The particles dispersed in the atmosphere eventually being deposited on the ground, destroying public property and private due to corrosive chemical composition. According to studies by Cetesb, the picture is worrying in view have already been found exceeded the maximum levels of air quality standards. Given this situation, action was filed by the President of the Federative Republic of Brazil in the face of the Mayor of the city of Santos, which enacted a law prohibiting the installation of bulk terminals in the Ponta da Praia region. In the present work, said the question of the triple responsibility of polluters and the importance of preserving the environment for present and future generations, highlighting the importance of the good inherent in human life, which can not be relegated to the background in face of economic interests.